Co-expression in Helicobacter pylori of cagA and non-opsonic neutrophil activation enhances the association with peptic ulcer disease. Issue 4 (1st April 2000) - Danielsson, D; Farmery, S M; Blomberg, B; Perry, S; Rautelin, H; Crabtree, J E
Abstract : Aims —To investigate the association of cagA positivity and non-opsonic neutrophil activation capacity in wild-type Helicobacter pylori strains with peptic ulcer disease or chronic gastritis only. Methods — Helicobacter pylori were isolated from antral biopsies of 53 consecutive patients with chronic antral gastritis, of whom 24 had peptic ulcer disease endoscopically. The presence of cagA, a marker for the cag pathogenicity island, was determined by polymerase chain reaction with specific oligonucleotide primers, and non-opsonic neutrophil activation capacity by luminol enhanced chemiluminescence. Results —The cagA gene was present in 39 of 53 (73.6%) strains, 20 of which (83.3%) were from the 24 patients with peptic ulcer disease and 19 (65.5%) from the 29 patients with chronic gastritis only. Non-opsonic neutrophil activation was found in 29 (54.7%) strains, 16 of which (66.7%) were from patients with peptic ulcer disease, and 13 (44.8%) from those with chronic gastritis. Non-opsonic neutrophil activation was found more frequently in cagA + than cagA − strains (59% v 42.9%). Whereas four of the 14 cagA − strains and eight of the 24 non-opsonic neutrophil activation negative strains were from patients with peptic ulcer disease, only two of 24 (8.3%) peptic ulcer disease strains expressed neither cagA nor non-opsonic neutrophil activation. The cagA gene and non-opsonic neutrophil activation capacity were co-expressed in 14 of 24 (58.3%) strains from patients with peptic ulcer disease, and in nine of 29 (31%) strains from individuals with chronic gastritis. Conclusions —Positivity for cagA and non-opsonic neutrophil activation occur independently in wild-type H pylori strains. However, co-expression of the two markers enhanced the prediction of peptic ulcer disease.